hUC-MSC Combined with DHEA Alleviates Ovarian Senescence in Naturally Aging Mice through Enhancing Antioxidant Capacity and Inhibiting Inflammatory Response - Chun-Yi Guan; Dan Zhang; Xue-Cheng Sun; Xu Ma; Hong-Fei Xia (Hindawi Limited, 2024)
The ovary is an important organ for women to maintain reproductive and endocrine functions. Ovarian aging can lead to female reproductive aging, which is a key factor causing rapid aging of the female body. Umbilical cord-derived MSCs (UC-MSCs) play a therapeutic role in various degenerative diseases. Dehydroepiandrosterone (DHEA) is widely used in the treatment of reversing oocyte quality. However, it is unclear whether UC-MSCs combined with DHEA supplementation can improve ovarian senescence in naturally aging mice. To address this question, we studied the influence of the combination of human UC-MSCs (hUC-MSCs) and DHEA on ovarian morphology and function in naturally aging mice. The results showed a significant augmentation in the number of primary follicles, as well as a significant upregulation of estradiol (E2), follicle-stimulating hormone (FSH), and anti-Mullerian hormone (AMH) hormone levels, and a significant increase in survival rate in naturally aging mice treated by hUC-MSCs and DHEA. Moreover, the combination of hUC-MSCs and DHEA significantly reduced the reactive oxygen species (ROS) level and downregulated the expression levels of proinflammatory factors IL-6, IL-18, and TNF-α. Furthermore, the PI3K/AKT/mTOR pathway was inhibited. Conclusively, the combination therapy of hUC-MSC + DHEA contributed to restore ovarian function in aging mice and extend their lifespan by restoring hormone levels and inhibiting inflammatory factors.